Knowledge in translation global patterns of scientific exchange, 1000-1800 CE - Manning, Patrick 1941-; Owen, Abigail; Burnett, Charles 1951- (University of Pittsburgh Press, 2018)
Intro -- Contents -- Foreword by Charles Burnett -- Preface -- Acknowledgments -- Introduction. Knowledge in Translation / Patrick Manning -- Part I. Mapping the Earth -- Chapter 1. The Geographical Concept of the Catalan mappamundi / Katrin Kogman-Appel -- Chapter 2. Interpretation, Intention, and Impact: Andalusi Arab and Norman Sicilian Examples of Islamo-Christian Cartographic Translation / Karen Pinto -- Chapter 3. Mountains of the Moon, Lakes in the Sun, and Sinus Gangeticus / Rila Mukherjee -- Chapter 4. The Global and the Maritime: Divergent Paradigms for Understanding the Role of Translation in the Emergence of Early Modern Science / Robert Batchelor -- Part II. Constructing Society -- Chapter 5. Charting China in the Thirteenth-Century World: The First English Translation of Zhu fan zhi and Its Recipients in China in the 1930s / Huei-Ying Kuo -- Chapter 6. The Case of Bingata: Trafficking Textile Art and Technique across the East China Sea / BuYun Chen -- Chapter 7. Mapping the Tracks of Yu: Yellow River Statecraft as Science and Technology, 1200-1600 / Ruth Mostern -- Part III. Advancing Health and Welfare -- Chapter 8. Animal Remedies in Space and Time: The Case of the Nail of the Great Beast / Irina Podgorny -- Chapter 9. Translating Heaven: Divination and Political Authority under the Yuan Dynasty / Francesca Fiaschetti -- Chapter 10. Between Local and Universal: Translating Knowledge in Early Modern Ottoman Plague Treatises / Nükhet Varlık -- Chapter 11. Transposing Knowledge: Beyond Translation in the Medieval Islamic and Japanese Medical Literary Traditions / M. A. Mujeeb Khan -- Part IV. Charting the Skies -- Chapter 12. The Nesting Hypothesis for Planetary Distances and Its Persistence over the Centuries and across Cultures / Bernard R. Goldstein and Giora Hon